What Drives Mortgage Default Risk in Europe and the U.S.? - Gross, Marco; Ding, Xiaodan; Tereanu, Eugen; Tressel, Thierry (Washington, D.C. : International Monetary Fund, 2022)
We present an analysis of the sensitivity of household mortgage probabilities of default (PDs) and loss given default (LGDs) on unemployment rates, house price growth, interest rates, and other drivers. A structural micro-macro simulation model is used to that end. It is anchored in the balance sheets and income-expense flow data from about 95,000 households and 230,000 household members from 21 EU countries and the U.S. We present country-specific nonlinear regressions based on the structural model simulation-implied relation between PDs and LGDs and their drivers. These can be used for macro scenario-conditional forecasting, without requiring the conduct of the micro simulation. We also present a policy counterfactual analysis of the responsiveness of mortgage PDs, LGDs, and bank capitalization conditional on adverse scenarios related to the COVID-19 pandemic across all countries. The economics of debt moratoria and guarantees are discussed against the background of the model-based analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Banks and Their Policies; Economics; General Financial Markets; Macroeconomics; Multiple or Simultaneous Equation Models